Rancang Bangun Modul Pembelajaran Elektronika Digital Dalam Meningkatkan Efisiensi Pembelajaran Mahasiswa - Rezar, Habil; Yuwono Thaaram, Medi; Riyanto, Agus (Electrical Network Systems and Sources, 2025)
This research aims to develop learning methods at Pontianak State Polytechnic to improve practicum efficiency and student understanding in digital electronics courses. The research includes making learning modules in the form of trainers, antibounce switches, system trials, and tool demonstrations. The developed module is equipped with a guidebook and includes power blocks, inputs, outputs, circuits, as well as guidebooks with logic, combinational, and sequential gate circuits. Data was collected through testing the efficiency of the module by comparing the usage time of the module and IC with the protoboard, as well as a survey to 3rd semester Electrical Engineering students using Google Forms. Quantitative descriptive data analysis shows that assembly with the module is faster than with manual IC. The module feasibility test results showed a percentage of 88% on material, 89% on technical, 92% on feasibility, and 91% on benefits, indicating that the module is very feasible to use as a companion to digital electronics courses.Keywords: Learning Module, Digital Electronics, Logic Gate, Combinational Circuit, Sequential Circuit